Pengaruh Coping Strategy Terhadap Produktivitas Pembelajaran Mahasiswa - Samdya, Rapif; Alviansyah, Faiq Fauzan; Meishinta, Dina; Hasan, Muhammad Abil (Universitas Medan Area, 2024)
The study aimed to investigate the influence of coping strategy on learning productivity by quantitative method. 102 undergraduate students participated in the study. Each respondent has distributed the questionnaire (google form) comprising The Coping Self-Efficacy Scale (CSE) and The College Student Experiences Questionnaire (CSEQ) as instruments. The result indicated that there was a positive significant influence of coping strategy on learning productivity (β = 0,279; p 0,05). The implication, limitation, and suggestion of study will be addressed in the following section.